Antibiotic potentiating action of α-PINENE and borneol against EPEC and ETEC sorotypes. (January 2022) - Leite-Sampaio, Nadghia F.; Gondim, Cicera Natalia F.L.; de Souza, Celestina E.Sobral; Coutinho, Henrique D.M.
Abstract: Escherichia coli is considered the main cause of intestinal and extra-intestinal infections, they have virulence mechanisms in different pathotypes and the ability to receive or transmit antimicrobial resistance genes. The aim of this work was to investigate the antibacterial and antimicrobial modulating activity of α-pinene and borneol against E. coli and enteropathogenic (EPEC) and enterotoxigenic (ETEC) serotypes. The broth microdilution methodology with multidrug-resistant Escherichia coli, EPEC and ETEC was used to determine the Minimum Inhibitory Concentration (MIC) and evaluation of the modulating activity of antibiotics (ciprofloxacin, sulfamethoxazole-trimethoprim and metronidazole) of α-pinene and borneol. It was concluded that α-pinene and borneol showed a low antimicrobial action against multi-resistant E. coli, however, this action was not observed against the EPEC and ETEC serotypes. A synergistic action of borneol associated with ciprofloxacin against ETEC was noted. Highlights: The α-pinene and borneol showed a low antimicrobial action against MDR E. coli . The α-pinene and borneol showed a low antimicrobial action against EPEC and ETEC. Synergism was observed associating the substances with ciprofloxacin against ETEC.